Translating conversational implicatures in English movies and series into Arabic: can floutings be captured? - Hadeel Saed; Ahmad S. Haider; Mohammad Albarakati; Sausan Abu Tair; Mohammad Alqatawna (Humanities & Social Sciences Communications)
Abstract This paper examines how flouts and violations of conversational maxims are represented in translation and how this influences the different types of translational equivalence. A number of scenes from audiovisual media where there is a gap between one character’s intended meaning and another’s reply were examined by comparing the employment of conversational maxims in the source and target text. Additionally, the relation between the employed translation strategies, equivalence type, and the representation of the maxims was analyzed. The results showed that audiovisual translators tend to reduce ambiguity through strategies like addition and explicitation, which alters the features of the maxims found in the source text. Moreover, linguistic differences also make retaining ambiguity a challenge. Furthermore, while functional equivalence is often seen as the ideal type to convey the sense of a text, in cases where the text contains double meanings, the rendition of sense is no longer straightforward. As a result, translators must employ compensational strategies to maintain the ambiguity or explain its existence. The study concludes that the translators must pay attention to nuance to choose the best equivalents and phrasings for each given situation since even slight changes may change the implicatures of the text.